The Role of Innate Lymphoid Cells in Chronic Respiratory Diseases - Hsu, Amy T.; Gottschalk, Timothy A.; Tsantikos, Evelyn; Hibbs, Margaret L. (Frontiers in Immunology, 2021)
The lung is a vital mucosal organ that is constantly exposed to the external environment, and as such, its defences are continuously under threat. The pulmonary immune system has evolved to sense and respond to these danger signals while remaining silent to innocuous aeroantigens. The origin of the defence system is the respiratory epithelium, which responds rapidly to insults by the production of an array of mediators that initiate protection by directly killing microbes, activating tissue-resident immune cells and recruiting leukocytes from the blood. At the steady-state, the lung comprises a large collection of leukocytes, amongst which are specialized cells of lymphoid origin known as innate lymphoid cells (ILCs). ILCs are divided into three major helper-like subsets, ILC1, ILC2 and ILC3, which are considered the innate counterparts of type 1, 2 and 17 T helper cells, respectively, in addition to natural killer cells and lymphoid tissue inducer cells. Although ILCs represent a small fraction of the pulmonary immune system, they play an important role in early responses to pathogens and facilitate the acquisition of adaptive immunity. However, it is now also emerging that these cells are active participants in the development of chronic lung diseases. In this mini-review, we provide an update on our current understanding of the role of ILCs and their regulation in the lung. We summarise how these cells and their mediators initiate, sustain and potentially control pulmonary inflammation, and their contribution to respiratory diseases such as chronic obstructive pulmonary disease (COPD) and asthma.